Environmental determinants of household microbial and allergen levels in the Greater Taipei Area. (15th February 2023) - Phiri, Yohane V.A.; Wu, Meei-Maan; Chen, Yi-Hua; Zou, Ming-Lun; Jiang, Chuen-Bin; Wu, Chih-Da; Huang, Hsiao-Chun; Lung, Shih-Chun Candice; Chien, Ling-Chu; Lo, Yu-Chun; Lee, Fang-Yu; Chao, Hsing Jasmine
Abstract: People spend most of their time indoors, where they may be exposed to various microorganisms and allergens. In this cross-sectional study, we investigated the relationship between indoor microbial and allergen levels and indoor and outdoor household environmental characteristics. Participants were recruited from an ongoing cohort study in the Greater Taipei Area. Questionnaire administration and environmental sampling were conducted during home visits. Samples were collected from children's bedrooms, living rooms, kitchens, and outdoor areas (balconies) and analyzed for fungal spores, house dust mite allergens (Der p 1 and Der f 1), endotoxin, and cockroach allergens (Bla g 1). Indoor temperature and relative humidity were also measured, and the land-use characteristics and points of interest surrounding the residences were evaluated within specified radii. The mean levels of outdoor air pollutants were then estimated, and multiple regression analysis was performed to investigate the predictors of indoor microbial and allergen levels. In total, 136 homes were analyzed. The results indicated that dog ownership, air purifier use, and floor cleaning frequency were major predictors of indoor microbial and allergen levels. Moreover, proximity to parks, roads, and forests was associated with elevated levels of indoor microorganisms and allergens. Our results demonstrated that indoor concentrations of certain microorganisms and allergens tended to increase in households located within neighborhoods with particular characteristics. Overall, our research findings contribute to housing intervention protocols and policies aimed at reducing exposure to indoor microorganisms and allergens. Future studies should longitudinally investigate the health effects of indoor microorganisms and allergens. Highlights: The presence of dogs and potted plants was associated with indoor microbial levels. Living near parks or roads was positively related to indoor microbial levels. Regular cleaning and removal of potential sources improve household air quality.